Effect of atorvastatin on systolic and diastolic function in patients with heart failure with reduced ejection fraction (HFrEF) - Faris Zvizdić; Edin Begić; Mirza Dilić; Šekib Sokolović; Orhan Lepara (Medicinski glasnik, 2021)
Aim: To investigate the benefit of high-dose lipophilic statin therapy on cardiac remodelling, function and progression of heart failure (HF) in patients with ischemic heart disease. Methods: A total of 80 patients with ischemic HF diagnosis were followed during 6 months, and they were divided in two groups. First group (n=40) was treated by high-dose lipophilic statin therapy (atorvastatin 40 mg) and conventional therapy for HF, while the second group (n=40) had no atorvastatin in the therapy. Results: In the beginning of study, from all of the observed parameters, only the ratio of flow rates in early and late diastole (E/A ratio) differed between the test groups (p=0.007). After six months, a statistically significant increase in left ventricular end-diastolic diameter (LVIDD) in patients who had not been treated with atorvastatin was found. In the patients treated with atorvastatin, there was a significant reduction in basal right ventricle diameter in diastole and systole (p<0.001 and p<0.001, respectively), and in tricuspid annular plane systolic excursion (TAPSE) (p<0.001); there was a reduction in LVIDD (p<0.001), and an increase of ejection fraction of the left ventricle according to Teicholtz and Simpson (p<0.001 and p<0.001, respectively). Also, there was an increase of deceleration time of early diastolic velocity (DTE) (p<0.05) and a decrease of isovolumic relaxation time (IVRT) (p<0.001). Conclusion: The reduction in the right and left ventricle diameters was noted after the six-month atorvastatin therapy. Atorvastatin in the therapy resulted in increased EFLV and better systolic function and should be a part of a therapeutic modality of HF.
Keywords: heart failure; hydroxymethylglutaryl-CoA reductase inhibitors; therapeutics